Psychogenic amnesia: implications for diachronic sense of self - Marques, Beatriz Sorrentino (2019)
Traditionally the issue of personal identity has considered as the question about what makes one the same across time. Recently though, attention to one’s own phenomenal experience has brought a new perspective to the debate. In light of this change of perspective, Klein suggests that individuals with retrograde episodic amnesia retain a notion of who they are, as well as having sense of continuity. He, therefore, argues that episodic memory is not necessary for a diachronic sense of self. I challenge Klein’s conclusion by pointing out that there are more extreme kinds of amnesia—psychogenic amnesia—that seem problematic to his proposal that sense of continuity is enough for a diachronic sense of self. This is the case because some instances of psychogenic amnesia are cases of dissociative amnesia, which show that having continuous conscious experience does not solve the issue.